Record of America : a reference history of the United States - McCarthy, Joseph F. X. (New York : Scribner, 1974)
Includes alphabetically arranged articles on important events and people in United States history and contemporary documents and illustrations pertinent to each topic.
v. 1. A-CI -- v. 2. CI-FO -- v. 3. FO-KE -- v. 4. KE-M -- v. 5. N-PR -- v. 6. PR-SM -- v. 7. SM-UR -- v. 8. UT-Z -- v. 9. Resource units 1-4 -- v. 10. Resource units 5-8.
Includes bibliographical references.
Keywords: United States -- History -- Encyclopedias, Juvenile; United States -- Biography -- Juvenile literature; United States -- History -- Encyclopedias; United States -- Biography -- Encyclopedias